The Implementation of Adiwiyata School Culture Development - Kholis, Nur; Indriharta, Lilik; Mufidah, Nuril (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe and analyze the implementation and cultural development of the adiwiyata school in MI Perwanida, Blitar City. This type of research is qualitative with a case study approach. The subjects of this study included school principals, teachers, students, parents, class associations (paguyuban), and school committees. Meanwhile, the object of implementation and the steps to develop adiwiyata school culture. Relevant data is collected using in-depth interviewing techniques, documentation, and observation. To determine the validity of the data using inspection techniques; credibility, transferability, dependability, and confirmability. Data analysis techniques are carried out starting with data collection, data display, data reduction, conclusion drawing. The results of the study indicate that; First, the implementation of adiwiyata school culture is carried out through several stages; mapping themes to be integrated into the material on all subjects; make regulations that are binding on all stakeholders both written and unwritten; and provide gifts and punishments for all perpetrators. Second, steps to develop the support of school stakeholders are carried out through several activities, namely; form a development team, coordinate and implement programs, and evaluate programs.